2022
DOI: 10.1021/acs.jpcb.2c03745
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Directionality of S···O/N Chalcogen Bond and Its Interplay with Weak C–H···O/N/S Hydrogen Bond Using Molecular Electrostatic Potential

Abstract: The directionality of the chalcogen bond (Ch-bond) formed by S and its interplay with other weak interactions have important chemical and biological implications. Here, dimers made of CH 3 −S−X and O/N containing nucleophiles are studied and found to be stabilized by coexisting SBased on experimentally accessible electron density and molecular electrostatic potentials (MESPs), we showed that reciprocity between S•••O/N and C−H•••O/N interactions in the stability of cumulative molecular interaction (ΔE) was dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 84 publications
0
7
0
Order By: Relevance
“…We believe that the revolutionary improvement in the resolution of 3D structural data of proteins determined using cryoEM will aid in the identification of unconventional noncovalent interactions in proteins and reveal new roles of these interactions in protein function. With many more protein structures being determined at very- and ultra-high resolution, use of charge-density analysis combined with detailed quantum chemical calculations, such as Atoms In Molecule analysis, will provide unprecedented insights into the nature and function of noncovalent interactions in proteins. ,, We believe that with newer and improved experimental and computational techniques being used for probing noncovalent interactions in small molecules and proteins, our understanding of the nature of these interactions, their role, and significance is only on the rise.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We believe that the revolutionary improvement in the resolution of 3D structural data of proteins determined using cryoEM will aid in the identification of unconventional noncovalent interactions in proteins and reveal new roles of these interactions in protein function. With many more protein structures being determined at very- and ultra-high resolution, use of charge-density analysis combined with detailed quantum chemical calculations, such as Atoms In Molecule analysis, will provide unprecedented insights into the nature and function of noncovalent interactions in proteins. ,, We believe that with newer and improved experimental and computational techniques being used for probing noncovalent interactions in small molecules and proteins, our understanding of the nature of these interactions, their role, and significance is only on the rise.…”
Section: Discussionmentioning
confidence: 99%
“…A more comprehensive analysis revealed that the divalent S preferred to approach the π region over the lone pair region of carbonyl O, indicating the importance of directionality for the formation of the interaction in proteins . A recent study showed that this directional selectivity originates from the electrostatic and cooperative nature of the Ch-bond . Also, 1.3% and 8.9% of methionine and cysteine in proteins could participate in Ch-bond formation, respectively, suggesting their role in stabilizing protein structures .…”
Section: σ-Hole Interactionmentioning
confidence: 99%
“…Hence, we conclude that S-mediated Ch- and H-bonds, like other weak interactions, are an essential aspect of the energy landscape in protein folding that compensates for unfavourable conformational entropy changes through favourable interactions (Grantcharova et al, 2001 ; Dobson, 2003 ). Furthermore, we envisage that cooperativity among S-mediated and other weak interactions is likely to modulate their strengths with direct implications for protein function, which remains to be studied (Adhav et al, 2022 ). For example, we speculate that the propensity and strength of Ch-bonds would increase upon the delocalisation of lone-pair electron density of Cys-S γ to form an n → π* interaction with a vicinal carbonyl group (Kilgore and Raines, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…interactions, first studied by Rosenfield, involve a weak coordination bond between a lone pair of the heteroatom X and a σ-hole on the divalent S atom (Scheme ). The use of the S···X interaction as a driving force for organic supramolecular chromophore assembly in the solution phase has not been explored previously, although these interactions have been exploited in the assembly of organic semiconductors in the solid state, , supramolecular capsules, , and polymers in solution and to enhance intramolecular electron transfer rates in dye-sensitized solar cells …”
mentioning
confidence: 99%
“…We hypothesize that the sulfide group in P-S plays a key role in inducing π-stacking in the excited state. Given that divalent sulfide is known to engage in noncovalent interactions (S···X) by coordinating with heteroatoms X such as O, N, or S, an intermolecular S···X interaction is proposed to occur between P-S molecules. This intermolecular S···X interaction can be a factor contributing to the supramolecular organization of P-S .…”
mentioning
confidence: 99%